2016
DOI: 10.20944/preprints201608.0054.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multi-Omics Studies towards Novel Modulators of Influenza A Virus-Host Interaction

Abstract: Human influenza A viruses (IAVs) cause global pandemics and epidemics. These viruses evolve rapidly, making current treatment options ineffective. To identify novel modulators of IAV-host interactions, we re-analyzed our recent transcriptomics, metabolomics, proteomics, phosphoproteomics, and genomics/virtual ligand screening data. We identified 713 potential modulators targeting 199 cellular and two viral proteins. Anti-influenza activity for 48 of them has been reported previously, whereas the antiviral effi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…In order to extend our findings beyond SARS-CoV-2, we tested IFNa2a-based combinations against FluAV. Through completion of a literature review, we identified several drugs that could be combined with IFNa2a to inhibit FluAV infection in vitro [10, 33, 34]. We tested emetine, flavopiridol, camostat, obatoclax, SNS-032, gemcitabine, monensin, cycloheximide and pimodivir against human influenza A/Udorn/307/1972 in A549 cells.…”
Section: Resultsmentioning
confidence: 99%
“…In order to extend our findings beyond SARS-CoV-2, we tested IFNa2a-based combinations against FluAV. Through completion of a literature review, we identified several drugs that could be combined with IFNa2a to inhibit FluAV infection in vitro [10, 33, 34]. We tested emetine, flavopiridol, camostat, obatoclax, SNS-032, gemcitabine, monensin, cycloheximide and pimodivir against human influenza A/Udorn/307/1972 in A549 cells.…”
Section: Resultsmentioning
confidence: 99%
“…Integrative analyses that use information across these data modalities promise to deliver more comprehensive insights into the biological systems under study. Motivated by this, multi‐omics profiling is increasingly applied across biological domains, including cancer biology (Gerstung et al , ; Iorio et al , ; Mertins et al , ; Cancer Genome Atlas Research Network, ), regulatory genomics (Chen et al , ), microbiology (Kim et al , ) or host‐pathogen biology (Soderholm et al , ). Most recent technological advances have also enabled performing multi‐omics analyses at the single‐cell level (Macaulay et al , ; Angermueller et al , ; Guo et al , ; Clark et al , ; Colomé‐Tatché & Theis, ).…”
Section: Introductionmentioning
confidence: 99%
“…We also applied PTMProphet to Dataset #3, a phosphopeptide enriched dataset derived from human cells. We selected and reanalyzed the PRIDE repository identifier PXD001620, as originally presented and described in detail by Söderholm et al 46 . Briefly, the dataset is from human macrophage cells infected with influenza A virus.…”
Section: Resultsmentioning
confidence: 99%